2016
DOI: 10.2355/isijinternational.isijint-2015-561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alumina Morphology on the Clustering of Alumina Inclusions in Molten Iron

Abstract: Clustering of alumina inclusions during liquid processing of steel significantly influences its cleanliness and mechanical properties. We have therefore studied the effect of alumina inclusion morphology on their clustering behavior in molten iron. Alumina inclusions were extracted from iron samples taken at 1 min after Al addition. Dendritic, spherical, plate-like, faceted and clustered alumina inclusions were identified and their clustering degrees were measured. The clustering degree increases in the order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…In addition, the interaction between nonspherical inclusions, such as the faceted inclusions, and the refractory wall seems like a plane-plane type interaction. According to the research by Zheng et al, [57] this kind of interaction is stronger compared to a sphere-plane type interaction, namely, the interaction between a spherical inclusion and a refractory wall. This means that nonspherical inclusions may easily stick to the wall once they move close to the wall compared to spherical inclusions.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the interaction between nonspherical inclusions, such as the faceted inclusions, and the refractory wall seems like a plane-plane type interaction. According to the research by Zheng et al, [57] this kind of interaction is stronger compared to a sphere-plane type interaction, namely, the interaction between a spherical inclusion and a refractory wall. This means that nonspherical inclusions may easily stick to the wall once they move close to the wall compared to spherical inclusions.…”
Section: Discussionmentioning
confidence: 94%
“…There are several types of attraction forces between non-metallic inclusions. Figure 6 summarized three types of attraction force the Van der Waals force, the force due to the gas cavity and the capillary force, which have been estimated by Zheng et al [4]. The measured attraction force at the molten steel surface is calculated by Equation (2) and also plotted in this graph.…”
Section: Type Of Attraction Forcementioning
confidence: 95%
“…It has been indicated that bonding through the cavity bridge may be the main reason for alumina inclusions strongly agglomerating in liquid steel. Furthermore, Zheng et al investigated the attractive forces between different shapes of alumina inclusions based on the theory of spontaneous cavitation [4]. By calculating the rupture energy of a cavity bridge, Zheng et al [4] demonstrated that a faceted inclusion has the strongest attractive force, which was reflected in a plate-like, dendritic and spherical shape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolved oxygen reacts with aluminum in steel to precipitate alumina, forming a dense network adhered to the internal wall of the nozzle, as shown in Equation (6). Inclusions that come with the steel through the nozzle easily adhere to this initial network through surface tension and diffusion mechanisms [3] intensifying the problem. 2½Al Fe þ 3½O Fe ¼ hAl 2 O 3 i Fe (6) Regarding Ti additions to steel, it is generally known that nozzle clogging during casting Ti-stabilized ultralow-carbon steels (Ti-SULC) is more severe and takes shorter forming times than when casting low-carbon aluminum-killed steels (LCAKS).…”
Section: Introductionmentioning
confidence: 99%